Foreign Labour Migration: Levels and Trends - Kunwar, Laxman Singh (Cognition, 2021)
This paper is related with foreign labour migration at global, regional and national level. Every day the volume of labourmigratnts have been increased. The data related with foreign labour migration are not uniform due to various organizations working on it and different methods apply by them. This article is entirely related with secondary sources of information. More specifically, ILO, IOM, UNPD and UN data related with international and regional level and DOFE and MoLESS data are for national lwevel are used to analyze the level and trends of foreign labour migration. Differences in level of development between developed and developing countries as well as lack of proper human resources management policies and high unemployment rate and poverty in developing countries are major cause to increased level and trends of volume of foreign labour migration.